1983
DOI: 10.1115/1.3240959
|View full text |Cite
|
Sign up to set email alerts
|

Gas Flow Resistance Measurements Through Packed Beds at High Reynolds Numbers

Abstract: This research study indicates that the classical Reynolds number dependency of the coefficient of drag for gases forced into packed beds is not correct at high Reynolds numbers. Care must also be taken to account for boundary layer wall effects that occur when the ratio of test chamber diameter to bead particle diameter is too small. Included is a review of the literature pertaining to gaseous flow resistance in packed beds. An existing test facility used in a previous study was found unsatisfactory, and neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 4 publications
3
16
0
Order By: Relevance
“…Recall that the friction factor can be expressed as < 126,670 (1983) 0.38 < e < 0.44 a These authors use an inverse drag coefficient fs and not f, where X is a shape factor, where fs arid f, differ by the multiplicative modified Re number. However, as Jones and Krier (1983) where C 1 and C 2 are constants. Along these lines, Tallmadge (1970) suggests…”
Section: Critique Of Current Orthodoxymentioning
confidence: 99%
See 2 more Smart Citations
“…Recall that the friction factor can be expressed as < 126,670 (1983) 0.38 < e < 0.44 a These authors use an inverse drag coefficient fs and not f, where X is a shape factor, where fs arid f, differ by the multiplicative modified Re number. However, as Jones and Krier (1983) where C 1 and C 2 are constants. Along these lines, Tallmadge (1970) suggests…”
Section: Critique Of Current Orthodoxymentioning
confidence: 99%
“…Figure 4 shows the bed drag, Fv, both for the conventional as well as the proposed models. Though under ballistic conditions, the gases through the bed accelerate, both Kuo and Nydegger (1978) and Jones and Krier (1983) investigated bed drag under steady-state conditions. The proposed model makes provisions for the acceleration of the gases which is observed after the inception of the ballistic cycle.…”
Section: Improved Drag Resistance Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that, by minimizing the root-mean-square error (RMSE) between the data points and the proposed functional relationship, the accuracy in the prediction of the coefficient of drag of propellant beds can be improved. Ergun (1952), Kuo and Nydegger (1978), and Jones and Krier (1983) have proposed models relating coefficient of drag and Reynolds number for gas flow through packed beds over the ranges illustrated in Figure 1. Following Jones and Krier, the relation between friction factor and coefficient of drag may be represented as is = Fv[(I -*)/Re], where 0 is the porosity of the packed bed, F, the coefficient of drag, and Re the Reynolds number of the gas flow based on particle size, with particle size much less than tube diameter.…”
mentioning
confidence: 99%
“…Section 4 contains a summary and main conclusions. Ergun (1952), Kuo and Nydegger (1978), and Jones and Krier (1983) have proposed models relating coefficient of drag to Reynolds number for steady flow through packed beds of inert spheres. However, the correlations were developed under different experimental regimens.…”
Section: Introductionmentioning
confidence: 99%